1996
DOI: 10.1007/bf02550143
|View full text |Cite
|
Sign up to set email alerts
|

Perineal prostatic cancer seeding following urocut needle biopsy

Abstract: A case of perineal tumour seeding after needle core biopsy of prostatic cancer is presented. This rare complication of prostatic needle biopsy occurred following false-negative tissue sampling in a patient subsequently treated by irradiation therapy and total androgenic blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In all, 26 articles were identified reporting needle‐tract seeding after prostate biopsy. Two additional papers were found; one presenting a case of perineal seeding after radioactive seed brachytherapy for prostate cancer and a second describing the implantation metastasis of prostate cancer in a suprapubic cystostomy tube needle tract (Table ) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In all, 26 articles were identified reporting needle‐tract seeding after prostate biopsy. Two additional papers were found; one presenting a case of perineal seeding after radioactive seed brachytherapy for prostate cancer and a second describing the implantation metastasis of prostate cancer in a suprapubic cystostomy tube needle tract (Table ) .…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, bcl‐2 (B‐cell lymphoma 2) expression was high in initial biopsy, RP and recurrent perineal specimen. Our literature review has revealed that seeding can manifest even with intermediate‐ and low‐grade tumours. Hence the association with tumour differentiation is not clear.…”
Section: Risk Factors For Needle‐tract Seedingmentioning
confidence: 98%
See 1 more Smart Citation
“…Rare sites that have been reported to harbor metastases from prostatic carcinoma include the kidney, 4 testes, 5 adrenals, 6 orbit, 7 breast, 8 umbilicus, 9 skeletal muscle, 10 and central nervous system. 11,12 Although perineal seeding has been reported to occur along the needle track after transperineal biopsy from prostatic carcinoma, 13,14 and after minimally invasive treatment of prostatic carcinoma by brachytherapy 15 and cryosurgery, 16 we are unaware of any previous report of locally advanced cancer prostate presenting by a perianal swelling. Other rare presentations of primary or metastatic prostate cancer include visual changes, 7 Cushing's syndrome, 17 lumbosacral radiculopathy, 18 hypoglossal nerve palsy, 19 superior vena cava obstruction, 20 and generalized lymphadenopathy.…”
Section: Discussionmentioning
confidence: 93%